Irradiance Level Only Moderately Affects Thermal Bleaching in the Stony Coral Stylophora pistillata - Ronald Osinga; Emma van Veenendaal; Daniëlle S. L. Geschiere; Britt J. A. van Herpen; Saskia Oosterbroek (Oceans)
Light is considered an important co-factor in causing thermal bleaching in photosymbiotic corals. To quantify the effects of light strength on thermal bleaching, colonies of the stony coral Stylophora pistillata were experimentally subjected to a gradual increase in temperature (1 °C per 4 days) under two irradiance levels: 100 and 500 µmole quanta m−2 s−1. Corals kept under the same irradiance levels at a constant temperature of 26 °C were used as controls. The apparent photochemical yield ΔF/Fm′ of Photosystem II of the coral symbionts was monitored daily as an indicator for the onset of thermal bleaching, the onset of bleaching being defined as a steep decrease in ΔF/Fm′. In heat-treated corals incubated under the high irradiance of 500 µmole quanta m−2 s−1, the onset of bleaching occurred 26 days after the start of the heat ramp, at a temperature of 33 °C. ΔF/Fm′ in corals incubated under the low irradiance of 100 µmole quanta m−2 s−1 started to drop 1 day later at the same temperature. Before and after the observed drop in ΔF/Fm′, coral samples were taken for analysis of symbiont densities and levels of chlorophyll-a. At the onset of bleaching, symbiont densities and chlorophyll-a levels in heat-treated corals were not different from those of corals kept under control conditions. Three days after the onset of bleaching, symbiont densities and levels of chlorophyll-a in heat-treated corals had substantially decreased in comparison to controls. Under low irradiance, symbiont density and chlorophyll-a content were 84% and 76% lower than controls, respectively, whereas under high irradiance, symbiont density and chlorophyll-a content were 41% and 46% lower. These data suggest that damage to the photosystem in coral symbionts is the root cause of thermal bleaching in symbiotic corals, followed later by a collapse of the symbiosis. The role of light in augmenting thermal bleaching was only moderate, with a five-fold reduction in irradiance causing only a 1-day delay in bleaching. These results suggest that temperature is the main driver of bleaching in the studied coral.